Psychotropic Medication and Substance Use during Pregnancy by Women with Severe Mental Illness - Brameld, Kate J.; Jablensky, Assen; Griffith, Jenny; Dean, John; Morgan, Vera A. (Frontiers in Psychiatry, 2017)
Background Sociodemographic factors, alcohol and drug intake, and maternal health are known to be associated with adverse outcomes in pregnancy for women with severe mental illness in addition to their use of psychotropic medication. In this study, we describe the demographic characteristics of women hospitalized for severe mental illness along with their use of medication and other drugs during the pregnancy period. Methods A clinical case note review of women with psychosis who were hospitalized at the State Psychiatric Hospital in Western Australia during 1966–1996, gave birth between 1980 and 1992, and received psychiatric treatment during the pregnancy period. The mother’s clinical information was available from the case notes and the midwives record. The demographic characteristics of the mothers were described together with their hospitalization pattern and their medication and substance use during the pregnancy period. Results A total of 428 mothers with a history of severe mental illness were identified who gave birth during 1980–1992. Of these, 164 mothers received psychiatric care during the pregnancy period. One hundred thirty-two had taken psychotropic medication during this period. Mothers who were married, of aboriginal status or living in regional and remote areas appeared less likely to be hospitalized during the pregnancy period, while older mothers and those with a diagnosis of schizophrenia were more likely to be hospitalized. The number of mothers taking psychotropic medication in the first trimester of pregnancy was reduced compared to the previous 6 months. The decline in the number taking substances over the same period was not significant. In all, 16% of the women attempted suicide during the pregnancy period and 10% non-suicidal self-injury. Conclusion The women demonstrate a pattern of decreased use of psychotropic medication use from the period before pregnancy to the first trimester of pregnancy. Our data highlight the importance of women with severe mental illness receiving regular ongoing monitoring and support from their psychiatrist during pregnancy regarding the level of medication required as well as counseling with regard to substance use, non-suicidal self-injury, and attempted suicide.